Numerical study on the behaviour of end-plate beam-to-column connections under lateral impact loading. (3rd March 2020) - Al-Rifaie, Ali; Al-Husainy, Alaa S.; Shanbara, Hayder K.
A parametric study is presented in this paper based on validated finite element models that were built in the companion paper that investigates the behaviour of two types of beam-column connections named flush plate connection (FPC) and partial depth end-plate connection (PDEPC) under quasi-static and lateral impact loadings. In the current study, the FE models were validated against additional two specimens tested with thick plates under lateral impact loading to raise the accuracy of the models. Different parameters were investigated such as the effect of mass and velocity, number of bolts, projectile shape and boundary conditions. Moreover, the study was extended to predict the lateral impact response of another type of connections named extended end-plate connection. The numerical results manifested that using thick end-plate is unfavourable to resist the lateral impact loading. Also, the deformation mode is not influenced by changing the projectile configuration or the boundary conditions.